Modern German fairy stories - Dresser, Florence (My University, 1908)
Introduction: The following stories are translations from New German Fairy Stories (“Neuer Deutscher Marchenschatz, Sonderheft Der Woche”). August Scherl. Berlin 1905.
Citation: Dresser, Florence. Modern German fairy stories. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fairy Tales; German Literature; Translations; Handwritten; Graduating theses; Senior theses; Theses